A study on the prevalence of nomophobia and its associated factors among the medical students of a medical college in central Kerala - George, Greeshma; Vincent, Jose; B., Jacob George (International Journal Of Community Medicine And Public Health, 2023)
Background: Nomophobia is considered as the disorder of the 21st century. It can have various consequences on mental health, affecting work and school performance and generating little social interaction outside of the virtual one. The aim of the study was to assess the prevalence and determinants of nomophobia among medical students. Methods: A cross-sectional study was conducted among 294 students of a medical college of Kerala during the period December 2022-February 2023. The prevalence of nomophobia was assessed using the nomophobia questionnaire (NMP-Q). Severity of insomnia was assessed using Insomnia index questionnaire. Results: The prevalence of nomophobia among the participants was 99.6%. The grades of nomophobia showed no significant association between gender, age, year of study, average screen time and severity of insomnia. Conclusions: The high prevalence of nomophobia addresses the need for an urgent intervention.